Predviđena vrijednost TRIB3 kombinovana sa BMPR2 za velike nevoljne kardiovaskularne događaje u starijim koronalnim bolesnicima bolesti srca koji poduzimaju procentnu koronalnu intervenciju: Klinički značaj BMPR2 i TRIB3 kod bolesti koronarnih arterija - Zhang, Qiang; Dong, Aiqiao; Wang, Tian; Kang, Fei; Wang, Huan; Sun, Jing (Journal of Medical Biochemistry, 2025)
Background: This research aims to explore the correlation of Tribbles Pseudokinase 3 (TRIB3) and bone morphogenetic protein receptor type 2 (BMPR2) with coronary heart disease (CHD), as well as the evaluation value of the combined detection of the two for major adverse cardiovascular events (MACE) following percutaneous coronary intervention (PCI). Methods: The study enrolled 152 CHD patients (CHD group) who underwent PCI treatment between January 2023 and May 2024 and 136 healthy individuals (control group) who concurrently underwent physical examination in our hospital. The expressions of TRIB3 and BMPR2 in the serum of both groups were measured. The clinical implications of these two factors in CHD, along with their diagnostic value for CHD, were then analyzed. Subsequently, the CHD patients were subjected to a 6-month follow-up. During this period, the occurrence of MACE was recorded and the evaluation value of the combined detection of TRIB3 and BMPR2 for MACE was analyzed. Results: In the CHD group, the concentration of TRIB3 was significantly elevated compared to the control group, existing a notable decline in TRIB3 levels after treatment (P<0.05). In contrast, the level of BMPR2 in the CHD group was significantly lower than that of the control group, and it increased significantly following treatment (P<0.05). In the CHD group, TRIB3 and BMPR2 were closely correlated with cardiac troponin I (cTnI) and left ventricular ejection fraction (LVEF) (P<0.05). The combined detection of TRIB3 and BMPR2 had a diagnostic sensitivity of 76.32% and a specificity of 91.18% for CHD (P<0.05). The follow-up results showed that 25 patients experienced MACE. Compared with non-MACE patients, the post-treatment level of TRIB3 was significantly higher in MACE patients, while the level of BMPR2 was statistically lower (P<0.05). The diagnostic sensitivity and specificity of the combined detection of TRIB3 and BMPR2 for MACE were 60.00% and 90.55%, respectively (P<0.05). Conclusion: Both TRIB3 and BMPR2 demonstrated excellent evaluation effects on the occurrence of CHD and the incidence of MACE after PCI.